Efektivitas Kompres Dingin (Cryotherapy) terhadap Penurunan Nyeri pada Pasien Fraktur Humerus Dextra Post ORIF - Esthu Nastiti Sundari; Dyah Rivani; Iin Nurhidayah (Pusat riset dan Inovasi Nasional, 2026)
Fracture is a condition characterized by the disruption of bone continuity that often causes acute pain, especially in patients following Open Reduction and Internal Fixation (ORIF). Effective pain management is essential to support the recovery process and improve patient comfort during hospitalization. This study aimed to determine the effectiveness of cold compress therapy (cryotherapy) in reducing pain intensity in post-ORIF patients. This study used a case study method on a patient diagnosed with a right humerus fracture at PKU Muhammadiyah Bantul Hospital. Data were collected through interviews, interventions, and documentation using the PQRST method. Cryotherapy was administered once daily for three consecutive days using an ice bag applied to the painful area. The results showed a gradual decrease in pain intensity from scale 7 to 6 on the first day, 5 on the second day, and 4 on the third day. The patient also reported increased comfort after the intervention. These findings indicate that cryotherapy is effective as a non-pharmacological intervention in reducing postoperative pain and improving patient comfort.